Efficacy of Probiotic Supplements and Topical Applications in the Treatment of Acne: A Scoping Review of Current Results - Sutema IAMP; Latarissa IR; Widowati IGAR; Sartika CR; Ciptasari NWE; Lestari K (Journal of Experimental Pharmacology)
Ida Ayu Manik Partha Sutema,1,2 Irma Rahayu Latarissa,1,3 I Gusti Ayu Rai Widowati,2 Cynthia Retna Sartika,1,4 Ni Wayan Eka Ciptasari,5 Keri Lestari1,3,6 1Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, Indonesia; 2Clinical Pharmacy Study Program, Faculty of Health Sciences, Bali International University, Denpasar, Indonesia; 3Medication Therapy Adherence Clinic (MTAC), Universitas Padjadjaran, Sumedang, Indonesia; 4PT Prodia StemCell Indonesia, Central Jakarta, Jakarta, Indonesia; 5Ngoerah Sun Wellness and Aesthetic Center, Prof. Dr. I.G.N.G. Ngoerah Central General Hospital, Denpasar, Indonesia; 6Center of Excellence for Pharmaceutical Care Innovation, Universitas Padjadjaran, Sumedang, IndonesiaCorrespondence: Keri Lestari, Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, Indonesia, Email lestarikd@unpad.ac.idAbstract: Acne vulgaris is a prevalent dermatological condition characterized by comedones, papules, and pustules, with significant physical and psychological implications. Conventional treatments for this condition, including antibiotics and retinoids, face challenges, such as side effects and antibiotic resistance, necessitating alternative treatments. Recent studies show the potential of probiotics to modulate skin microbiome and alleviate acne symptoms. Therefore, this study aimed to consolidate evidence from randomized controlled trials (RCTs) and clinical investigations, evaluating the efficacy of probiotics in acne management. A comprehensive literature search was conducted across PubMed, Scopus, and Cochrane databases using several keywords, such as “probiotic”, “microbiome”, and “acne vulgaris”. Inclusion criteria are RCTs and clinical studies from 2009 to 2024 examining probiotics for acne treatment. Studies were selected, screened, and analyzed based on population, intervention, design, and results. Descriptive statistics were used to summarize study characteristics. Fifteen studies including 811 participants met the inclusion criteria. The studies tested various oral and topical probiotics, including Lactobacillus, Bifidobacterium, Bacillus, and Enterococcus strains, over treatment periods ranging from 4 to 12 weeks. The results showed that probiotics, reduced acne lesions, improved skin barrier function, and decreased inflammatory markers. Both oral and topical probiotics showed potential in balancing skin microbiome and reducing acne severity. Some studies reported outcomes comparable to conventional acne treatments, such as antibiotics and benzoyl peroxide. However, there is variability in individual responses to different probiotic strains, and potential side effects, though rare, have been reported in some cases. Probiotics presented a natural, effective alternative to conventional acne treatment. However, future studies are needed to determine optimal treatment protocols.Keywords: probiotics, skin microbiome, acne vulgaris, bacterial imbalance, inflammatory skin conditions